Design and characterization of the carbon fiber tube reinforced polymer composite for full ocean depth submersibles. (5th January 2022) - Zhang, Runbo; Li, Zihan; Sun, Qiuyu; Yu, Guocai; Wang, Xintao; Wu, Linzhi
Abstract: The large difference between in-plane and out-of-plane mechanical properties limits the application of traditional composite honeycombs in submersibles. In this work, the carbon fiber tube reinforced polymer composite (CTPC) which have lightweight characteristic and high hydrostatic strength is designed and manufactured. The combination between epoxy resin and carbon fiber tube inhibits the buckling failure and improves the bearing capacity of the tube. Resin binds carbon fiber tubes and forms a stable stress transmission path between them. The hydrostatic response of the CTPC has been investigated by simulation and test. The measured results show good agreement with the simulation. Due to its high hydrostatic bearing capacity and lightweight, the CTPC can be used as a new type of buoyancy material in submersibles. Graphical abstract: Image 1